Analysis Of Semantic In Lyn Lapid Songs - I Gede Neil Prajamukti Wardhana; Ida Bagus Made Juliana Raditha Oka; Ni Luh Desy Suari Dewi; Gek Wulan Novi Utami (Denpasar Institute, 2022)
Song is a short poem or other set of words set to music or meant to be sung. By listening to the songs, we can get knowledge about appreciating literature and the background of the song. The objective of this study is to analyze the lexical meanings and the contextual meaning in Lyn lapid song lyrics that are “In My Mind” and “Itsy Bitsy”. The aim of this discussion is to try to make sense of the song lyric from the side view of semantic meaning: lexical meaning and contextual meaning. The step to obtain the data is by collecting sources of the data from Lyn lapid song’s lyrics that are “In My Mind” and “Itsy Bitsy Spider” that has been posted in youtube. After that selected the lyric which contain of semantic, reads and listens to the lyrics to understand the content of the songs conducts and analyzes the collected data and makes conclusion.The result of this research is as follows: (1) related to the lexical meaning, while (2) related to the contextual meaning